2007
DOI: 10.1007/s11483-007-9038-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Oil/Monoglyceride Networks by Polarizing Near-Field Scanning Optical Microscopy

Abstract: Polarizing near-field scanning optical microscopy (NSOM) was applied for visualization of lipid coagel structures. The technique ensures obtaining polarization contrast images at micro-and nanoscale resolution. Comparison to the polarizing light microscopy images revealed that the same fractal structural organization persists also at submicron scale, at the level of primary ordered structures creation. Many long birefringent needle-shaped primary crystallites were imaged in the corn oil:monoglyceride samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 18 publications
12
28
0
Order By: Relevance
“…Similar results were reported by Lopez‐Martinez et al. () in a study of oleogels from MG and safflower oil, and by Kesselman and Shimoni (), who analyzed the microstructure of oleogels from MG and olive oil.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were reported by Lopez‐Martinez et al. () in a study of oleogels from MG and safflower oil, and by Kesselman and Shimoni (), who analyzed the microstructure of oleogels from MG and olive oil.…”
Section: Resultssupporting
confidence: 89%
“…3b). These structures were also observed before by Kesselman and Shimoni (2007) who attributed it to the presence of a b-coagel structure formed in olive oil-saturated monoglyceride samples. In our study, also unsaturated monoglycerides are present, but these are also known to crystallize easily in a b-polymorph in water-free systems (Vereecken, .…”
Section: Plmsupporting
confidence: 80%
“…On the other hand, the MG crystals are absolutely rosettelike or spherulitic as reported by Kesselman and Shimoni (2007) for corn oil-MG organogels. In contrast, in the same study (Kesselman and Shimoni, 2007), needle-like crystals were reported for virgin olive oil-MG organogels. Obviously, MG can form needle-like or rosette-like crystals, and the reason behind this phenomenon needs further investigation.…”
Section: Resultssupporting
confidence: 57%
“…The rheological properties of olive oilmonoglyceride organogels under deformations were investigated, and the oiling out effect of shearing was approved (Ojijo et al, 2004). The analyses of the morphology of olive oil-monoglyceride organogels have revealed needle-like crystals with 5-15 μm in length (Kesselman and Shimoni, 2007). Olive oil organogel was also prepared with a cross-linked β-lactoglobulin stabilized oil-in-water emulsion by Mezzenga (2011).…”
Section: Introductionmentioning
confidence: 99%